Wall cloth coating composition and application thereof
By optimizing the design of wall coating composition and negative oxygen ion slurry, the problems of VOC and static in PVC wall cloth production are solved, significantly improving the concentration and coverage area of negative oxygen ions, and improving the product quality of wall cloth and Application effect.
Patent Information
- Application Number
- CN202411371060.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
The existing PVC wall cloth production intercooled glue composite method is prone to VOC and static electricity, and the negative oxygen ion concentration and coverage area of the negative oxygen ion wall cloth are insufficient, which affects product quality and application effect.
Optimized wall coating compositions including PVC resin, dioctyl terephthalate, epoxy soybean oil, composite calcium-zinc stabilizer, stone powder, aluminum hydroxide, environmentally friendly flame retardants, titanium dioxide and stear Acid, combined with nano tourmaline powder and modified acrylic emulsion, uses N,N-dimethyl-β-hydroxyethyl octamide γ propyl Quaternary ammonium nitrate excites negative oxygen ions, significantly improving the negative ion concentration and coverage area.
The film formation quality and thermal patch composite effect of PVC film are improved, the generation of VOC and static electricity is avoided, the negative ion concentration and coverage area in the space are significantly improved, and the product quality and practical application effect of the wall cloth are improved.
Smart Images

Figure BDA0005067595740000031 
Figure BDA0005067595740000111 
Figure BDA0005067595740000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wall cloth, in particular to a wall cloth coating composition and application thereof. Background Art
[0002] Wall cloth is a kind of building interior wall decoration material pasted on the wall for decoration. According to its function, it can be divided into flame retardant wall cloth, anti-static wall cloth, mildew-proof wall cloth, waterproof and oil-proof wall cloth, anti-fouling wall cloth, multifunctional wall cloth, etc. Negative oxygen ion wall cloth is a new type of wall cloth that can release a large amount of negative oxygen ions that are beneficial to human physical and mental health. It is mainly composed of inorganic minerals and pure natural ingredients, has no toxic side effects, and has the function of permanently releasing hydroxyl negative ions.
[0003] At present, PVC wall cloth is mainly produced by a split method, which is to laminate the PVC film with the cross mesh cloth through cold glue lamination; however, the cold glue lamination method is prone to produce VOC and static electricity that consume negative oxygen ions, which will have an adverse effect on product quality. In addition, the existing negative oxygen ion wall cloth mainly adds natural mineral nano seagull stone, ancient sea rock, etc. as negative oxygen ion materials, which can release low concentrations of negative oxygen ions. At the same time, the coverage area of negative oxygen ions is limited, which greatly reduces the actual application effect of negative oxygen ion wall cloth.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a wall cloth coating composition and its application, which can improve the film-forming quality of the PCV film and the thermal bonding effect of the PCV film and the base cloth, avoid the generation of VOC and static electricity when preparing the wall cloth, and maximize the use of negative oxygen ion cathode materials to excite negative oxygen ions, thereby significantly improving the negative ion concentration and coverage area in the space.
[0006] The invention provides a wall cloth coating composition, comprising the following components in parts by weight: 100 parts of PVC resin, 30-35 parts of dioctyl terephthalate (DOTP), 4-6 parts of epoxidized soybean oil, 2-3 parts of composite calcium zinc stabilizer, 18-22 parts of stone powder, 28-32 parts of aluminum hydroxide, 4-6 parts of environmentally friendly flame retardant, 13-15 parts of titanium dioxide and 0.2-0.4 parts of stearic acid.
[0007] Preferably, the wall cloth coating composition of the present invention comprises the following components in parts by weight: 100 parts of PVC resin, 30-34 parts of dioctyl terephthalate (DOTP), 4-5 parts of epoxidized soybean oil, 2-2.5 parts of composite calcium zinc stabilizer, 18-20 parts of stone powder, 28-30 parts of aluminum hydroxide, 4-5 parts of environmentally friendly flame retardant, 13-14 parts of titanium dioxide and 0.2-0.3 parts of stearic acid.
[0008] Furthermore, the composite calcium zinc stabilizer includes a calcium zinc stabilizer and a barium zinc stabilizer, and the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer in the composite calcium zinc stabilizer is 1:(1-2).
[0009] The present invention also provides application of the wall cloth coating composition in preparing wall cloth.
[0010] Specifically, the preparation of the wall covering comprises the following steps:
[0011] S1: adding each component by weight into a high-stirring mixing device and stirring and mixing to obtain a mixture;
[0012] S2: conveying the mixed material to a mixing chamber for mixing, and conveying the mixed material to a twin-roll extruder for mixing to obtain a mixed material;
[0013] S3: The mixed material is conveyed to a laminating machine for laminating, and the PVC film formed by laminating is laminated onto the base fabric while hot, and then cooled by a cooling roller to obtain a wall cloth.
[0014] In step S1, the mixture is stirred and mixed at 40-50° C. for 4-6 minutes.
[0015] In step S2, the mixture is kneaded at 130-140° C. for 5-10 min; the mixing time is 3-5 min.
[0016] In step S3, the thermal bonding temperature is 165-185°C, preferably 170-180°C; in addition, after cooling, the process also includes: printing and embossing by a gravure printing machine; wherein the printing temperature is 80-120°C, such as 90-110°C, and the embossing temperature is 185-210°C, such as 200-210°C. The mass of the wall cloth is 300-450g / m 2 .
[0017] Furthermore, the preparation of the wall cloth also includes step S4: evenly coating the negative oxygen ion slurry on the surface of the wall cloth, drying and cooling, to obtain the negative oxygen ion wall cloth.
[0018] Specifically, the negative oxygen ion slurry includes the following raw materials in parts by weight: 10-20 parts of negative oxygen ion materials and 80-90 parts of printing media; preferably, the negative oxygen ion materials include the following raw materials in parts by weight: 45-55 parts of modified acrylic emulsion, 0.5-1.5 parts of defoaming agent, 1.5-2.5 parts of N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate, 25-35 parts of modified nano-tourmaline powder and 15-25 parts of versatate.
[0019] Furthermore, the modified nano-tourmaline powder is composed of nano-tourmaline powder and borate; wherein the weight ratio of the nano-tourmaline powder to the borate is (3-5):(5-7); and the particle size of the nano-tourmaline powder is 2000 mesh.
[0020] The preparation method of the negative oxygen ion material comprises: mixing the components by weight, and then stirring them evenly under ultrasonic conditions; wherein the stirring temperature is 30-40°C, and the stirring time is 20-40 minutes. The preparation method of the negative oxygen ion slurry comprises: mixing the components by weight, and then stirring them evenly; wherein the stirring speed is 1100-1300r / min, and the stirring mixing time is 5-15 minutes.
[0021] In step S4, the coating amount of the negative oxygen ion slurry is 20-25 g / m 2 ; Drying temperature is 110-120℃, and drying time is 20-25s.
[0022] Nano tourmaline has piezoelectric effect and pyroelectric effect, and has strong far-infrared radiation function; at the same time, temperature and pressure changes will also cause the potential difference of tourmaline crystals, ionizing the surrounding air, and the struck electrons act on the adjacent water and oxygen molecules and convert them into negative oxygen ions. Versatylene carbonate and modified acrylic emulsion are used as low-temperature dispersion and attachment carriers, compounded with defoaming agents, and stirred under constant temperature ultrasonic waves to activate and disperse nano tourmaline to the greatest extent, thereby improving the ability of nano tourmaline to release negative oxygen ions, greatly increasing the concentration of negative ions in the space.
[0023] The molecular formula of N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate is as follows:
[0024]
[0025] N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate can be evenly distributed in PVC and nano-tourmaline coatings. Its molecular structure and anionic properties enable it to eject negative oxygen ions into the air like a spring, making the dispersion of negative oxygen ions more uniform and extensive, significantly increasing the negative ion coverage area in the space. In addition, N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate and tert-butyl ester can improve the film-forming properties of wall cloth, making the appearance and quality of wall cloth better.
[0026] The implementation of the present invention has at least the following advantages:
[0027] 1. The present invention improves the film-forming quality of the PVC film by optimizing the composition of the wall cloth coating composition; at the same time, the PVC film formed by lamination is laminated onto the base cloth while hot, which can form a better lamination effect, good firmness and durability of lamination, and improve the product quality of the wall cloth;
[0028] 2. In the present invention, the PVC film is directly hot-bonded to the base fabric while it is hot when preparing the PVC film, which can effectively avoid the generation of VOC and static electricity during traditional cold glue bonding, and avoid the adverse effects of VOC and static electricity such as consumption of negative oxygen ions and impact on product quality;
[0029] 3. The present invention adopts the method of first normal printing and embossing and then processing the negative oxygen ion material when preparing the negative oxygen ion wall cloth, which can maximize the use of the negative oxygen ion material's ability to stimulate negative oxygen ions; in particular, by optimizing the composition of the negative oxygen ion material, the ability of nano-tourmaline to release negative oxygen ions can be maximized, thereby significantly improving the negative ion concentration and coverage area in the space. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0031] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The raw materials used in each embodiment are as follows:
[0034] PVC resin: Type V suspension PVC resin, model S-1000, viscosity 1.87-1.89, water content 0.05-0.08%, purchased from Beijing Zhonghe Yongchang Economic and Trade Co., Ltd.;
[0035] Epoxidized soybean oil: model HM-01AD, purchased from Suzhou Easeo New Material Technology Co., Ltd.;
[0036] Stone powder: model CC-902, oil absorption value 35-38%, moisture 0.04-0.08%, purchased from Guangxi Hezhou Kelong Powder Co., Ltd.;
[0037] Environmentally friendly flame retardant: purchased from Liuyang Baolin Electrical New Materials Co., Ltd.;
[0038] Modified acrylic emulsion: model EMX-6A, solid content 21-24%, pH value 7.5, purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.;
[0039] Nano tourmaline powder: particle size 2000 mesh, purchased from Beijing Senhai Oxygen Source Technology Co., Ltd.;
[0040] Defoaming agent: stearyl alcohol purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.
[0041] N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate: purchased from Polyli Chemical;
[0042] Water-based acrylic printing medium: model EMW, pH value 7.5-9.5, viscosity (No. 3 Zahn cup, 25° C.) 15-50 seconds, fineness better than 25 μm, purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.
[0043] Example 1
[0044] The present embodiment provides a wall cloth coating composition, comprising the following components in parts by weight: 100 parts of PVC resin, 32 parts of DOTP, 5 parts of epoxidized soybean oil, 2.5 parts of composite calcium zinc stabilizer, 20 parts of stone powder, 30 parts of aluminum hydroxide, 5 parts of environmentally friendly flame retardant, 14 parts of titanium dioxide and 0.3 parts of stearic acid; wherein the composite calcium zinc stabilizer is composed of a calcium zinc stabilizer and a barium zinc stabilizer, and the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer is 1:1.
[0045] Example 2
[0046] The present embodiment provides a wall cloth coating composition, comprising the following components in parts by weight: 100 parts of PVC resin, 30 parts of DOTP, 4 parts of epoxidized soybean oil, 2 parts of composite calcium-zinc stabilizer, 18 parts of stone powder, 28 parts of aluminum hydroxide, 4 parts of environmentally friendly flame retardant, 13 parts of titanium dioxide and 0.2 parts of stearic acid; wherein the composite calcium-zinc stabilizer is composed of a calcium-zinc stabilizer and a barium-zinc stabilizer, and the mass ratio of the calcium-zinc stabilizer to the barium-zinc stabilizer is 1:2.
[0047] Example 3
[0048] The present embodiment provides a wall cloth coating composition, comprising the following components in parts by weight: 100 parts of PVC resin, 34 parts of DOTP, 5 parts of epoxidized soybean oil, 2 parts of composite calcium zinc stabilizer, 18 parts of stone powder, 30 parts of aluminum hydroxide, 4 parts of environmentally friendly flame retardant, 13 parts of titanium dioxide and 0.3 parts of stearic acid; wherein the composite calcium zinc stabilizer is composed of a calcium zinc stabilizer and a barium zinc stabilizer, and the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer is 1:1.5.
[0049] Example 4
[0050] This embodiment provides a method for preparing a wall covering, and the steps are as follows:
[0051] 1. Prepare the mixture
[0052] Prepare the materials according to the composition of the wall cloth coating composition in Example 1.
[0053] Add each component to a high-stirring mixing equipment according to weight, and stir and mix at 45°C for 5 minutes; when adding materials, first add PVC resin, then add liquid components, premix for 2 minutes, then add other powder components, and mix at 45°C for 3 minutes to obtain a mixture.
[0054] 2. Preparation of semi-finished wall coverings
[0055] The above mixture was transported to the mixing chamber, the temperature was set to 135℃, and the mixing was carried out for 8 minutes. After the mixing was completed, the mixture was further transported to the twin-roll extruder for mixing for 4 minutes. After mixing, the material was quantitatively transported to the 4-roll film pressing machine for film pressing, and the film (i.e. PVC film) was hot-laminated onto the cross cloth while hot, and the hot-laminated temperature was 170℃. After cooling by the cooling roller, the semi-finished wall cloth roll was obtained.
[0056] 3. Printing and embossing
[0057] The semi-finished wall cloth is printed and embossed with different patterns and colors by a gravure printing machine. The printing temperature of each plate is controlled at 110° C. and the embossing temperature is controlled at 210° C. to obtain the semi-finished wall cloth.
[0058] Example 5
[0059] This embodiment provides a method for preparing a wall covering, and the steps are as follows:
[0060] 1. Prepare the mixture
[0061] Prepare the materials according to the composition of the wall cloth coating composition of Example 2.
[0062] Add each component by weight to a high-stirring mixing device, and stir and mix at 45°C for 8 minutes; when adding materials, first add the PVC resin, then add the liquid component, premix for 3 minutes, then add other powder components, and mix at 45°C for 5 minutes to obtain a mixture.
[0063] 2. Preparation of semi-finished wall coverings
[0064] The above mixture was transported to the mixing chamber, the temperature was set to 135℃, and the mixing was carried out for 8 minutes. After the mixing was completed, the mixture was further transported to the twin-roll extruder for mixing for 4 minutes. After mixing, the material was quantitatively transported to the 4-roll film press for film pressing, and the film was hot-laminated onto the cross cloth while hot, and the hot lamination temperature was 175℃. After cooling by the cooling roller, the semi-finished wall cloth roll was obtained.
[0065] 3. Printing and embossing
[0066] The semi-finished wall cloth is printed and embossed with different patterns and colors by a gravure printing machine. The printing temperature of each plate is controlled at 90°C and the embossing temperature is controlled at 205°C to obtain a semi-finished wall cloth with printed and embossed colors.
[0067] Example 6
[0068] This embodiment provides a method for preparing a wall covering, and the steps are as follows:
[0069] 1. Prepare the mixture
[0070] Prepare the materials according to the composition of the wall cloth coating composition in Example 3.
[0071] Add each component to a high-stirring mixing equipment according to weight, and stir and mix at 45°C for 7 minutes; when adding materials, first add PVC resin, then add liquid components, premix for 3 minutes, then add other powder components, and mix at 45°C for 4 minutes to obtain a mixture.
[0072] 2. Preparation of semi-finished wall coverings
[0073] The above mixture was transported to the mixing chamber, the temperature was set to 135℃, and the mixing was carried out for 8 minutes. After the mixing was completed, the mixture was further transported to the twin-roll extruder for mixing for 4 minutes. After mixing, the material was quantitatively transported to the 4-roll film pressing machine for film pressing, and the film was hot-laminated onto the cross cloth while hot, and the hot lamination temperature was 180℃. After cooling by the cooling roller, the semi-finished wall cloth roll was obtained.
[0074] 3. Printing and embossing
[0075] The semi-finished wall cloth is printed and embossed with different patterns and colors by a gravure printing machine. The printing temperature of each plate is controlled at 100°C, and the embossing temperature is controlled at 200°C to obtain a semi-finished wall cloth with printed and embossed colors.
[0076] Example 7
[0077] This embodiment provides a method for preparing a passive negative oxygen ion wall covering, and the steps are as follows:
[0078] 1. Preparation of negative oxygen ion cathode materials
[0079] The negative oxygen ion cathode material includes the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate, 30 parts of modified nano-tourmaline powder and 17 parts of tert-butyl vinyl carbonate; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 1:1.
[0080] The above materials were mixed according to weight ratio and in the order of adding the liquid component first and then the powder component, and stirred in an ultrasonic constant temperature bath at 35° C. for 30 minutes to obtain a negative oxygen ion cathode material.
[0081] 2. Preparation of negative oxygen ion slurry
[0082] 20 parts of the above negative oxygen ion cathode material were mixed with 80 parts of aqueous acrylic printing medium, and stirred at 1200 r / min for 10 minutes to obtain negative oxygen ion slurry for later use.
[0083] 3. Preparation of passive negative oxygen ion wall covering
[0084] The slurry was evenly applied to the front of the semi-finished wall cloth printed embossing product of Example 4 by squeezing using an upper silicone roller and a lower silicone roller with a hardness of 72 on a printing machine, and the coating amount was 20 g / m 2 ; Then, according to the depth of the wall cloth texture, the vehicle speed was set to 20 m / min and the temperature to 145°C. After drying at 120°C for 20 seconds, it was cooled and trimmed, and then divided into 30 m / rolls according to the standard to obtain passive negative oxygen ion wall cloth.
[0085] The passive negative oxygen ion wall cloth prepared in this embodiment has good film-forming properties and no adverse phenomena in appearance. The appearance and radiation properties all meet the relevant quality requirements of the wall cloth.
[0086] Example 8
[0087] This embodiment provides a method for preparing negative oxygen ion wall cloth, the steps are as follows:
[0088] 1. Preparation of negative oxygen ion cathode materials
[0089] The negative oxygen ion cathode material includes the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate, 15 parts of nano tourmaline powder (2000 mesh) and 17 parts of versatate.
[0090] The above materials were mixed according to weight ratio and in the order of adding the liquid component first and then the powder component, and stirred in an ultrasonic constant temperature bath at 35° C. for 30 minutes to obtain a negative oxygen ion cathode material.
[0091] 2. Preparation of negative oxygen ion slurry
[0092] 20 parts of the above negative oxygen ion cathode material were mixed with 80 parts of aqueous acrylic printing medium, and stirred at 1200 r / min for 10 minutes to obtain negative oxygen ion slurry for later use.
[0093] 3. Preparation of negative oxygen ion wall covering
[0094] The slurry was evenly applied to the front of the semi-finished wall cloth printed embossing product of Example 4 by squeezing using an upper silicone roller and a lower silicone roller with a hardness of 72 on a printing machine, and the coating amount was 20 g / m 2 ; Then, according to the depth of the wall cloth texture, the vehicle speed was set to 20 m / min and the temperature to 145°C. After drying at 120°C for 20 seconds, it was cooled and trimmed, and then divided into 30 m / rolls according to the standard to obtain passive negative oxygen ion wall cloth.
[0095] Comparative Example 1
[0096] The wall cloth coating composition of this control example includes the following components in parts by weight: 100 parts of PVC resin, 32 parts of DOTP, 5 parts of epoxidized soybean oil, 1.5 parts of composite calcium-zinc stabilizer, 20 parts of stone powder, 30 parts of aluminum hydroxide, 5 parts of environmentally friendly flame retardant, 14 parts of titanium dioxide and 0.3 parts of stearic acid; wherein the composite calcium-zinc stabilizer is composed of a calcium-zinc stabilizer and a barium-zinc stabilizer, and the mass ratio of the calcium-zinc stabilizer to the barium-zinc stabilizer is 1:1.
[0097] The method of Example 4 was adopted to prepare the semi-finished printed embossed wall cloth. The results showed that the semi-finished printed embossed wall cloth of this control example had poor stability and severe yellowing.
[0098] Comparative Example 2
[0099] Except that the PVC film prepared in Example 4 is laminated to the cross cloth by cold glue lamination, the rest is basically the same as Example 4.
[0100] The method of Example 7 is used to evenly apply the negative oxygen ion slurry to the front of the printed embossed semi-finished wall cloth prepared in this reference example, and then cooled and trimmed after drying (that is, except for using the printed embossed semi-finished wall cloth prepared in this reference example to replace the printed embossed semi-finished wall cloth of Example 7, the other process steps and parameters are the same as those of Example 7) to obtain passive negative oxygen ion wall cloth.
[0101] Comparative Example 3
[0102] Except that the negative oxygen ion cathode material of Example 7 is replaced by a negative oxygen ion material, the rest is basically the same as Example 7 to obtain a negative oxygen ion wall cloth.
[0103] The negative oxygen ion material composition of this control example is as follows: 20 parts of negative oxygen ion material (mineral powder produced in Lingshou County, purchased from the normal market) are mixed with 80 parts of water-based acrylic printing medium, and stirred at 1200r / min for 10 minutes to obtain negative oxygen ion slurry.
[0104] Comparative Example 4
[0105] Except for the different composition of the negative oxygen ion cathode material, the rest is the same as Example 7.
[0106] The negative oxygen ion material of this control example includes the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoaming agent, 30 parts of modified nano-tourmaline powder and 19 parts of tert-butyl vinyl carbonate; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 1:1.
[0107] The negative oxygen ion wall cloth prepared in this control example has poor film-forming properties and has spots, cracks and other undesirable phenomena on the appearance.
[0108] Test Example 1
[0109] The negative ion performance of the negative oxygen ion wall coverings of Examples 7, 8 and Comparative Examples 2-4 was tested using the following method:
[0110] Negative ion concentration: using the material-induced air ion test method;
[0111] Negative ion free distance: Post 1 square meter of negative oxygen ion wall cloth, test the concentration of negative oxygen ions at different distances in a closed room, and the average value reaches 500ions / cm 3 The above position is the free distance of negative oxygen ions.
[0112] The results are shown in Table 1.
[0113] Table 1 Quality test results of each negative oxygen ion wall cloth
[0114]
[0115]
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A wall cloth coating composition, characterized in that: The invention comprises the following components in parts by weight: 100 parts of PVC resin, 30-35 parts of DOTP, 4-6 parts of epoxy soybean oil, 2-3 parts of composite calcium zinc stabilizer, 18-22 parts of stone powder, 28-32 parts of aluminum hydroxide, 4-6 parts of environmentally friendly flame retardant, 13-15 parts of titanium dioxide and 0.2-0.4 parts of stearic acid.
2. The wall cloth coating composition according to claim 1, characterized in that: The composite calcium zinc stabilizer comprises a calcium zinc stabilizer and a barium zinc stabilizer, and the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer in the composite calcium zinc stabilizer is 1:(1-2).
3. Use of the wall cloth coating composition according to any one of claims 1 to 2 in the preparation of wall cloth.
4. The use according to claim 3, characterized in that: The preparation of wall coverings includes the following steps: S1: adding each component by weight into a high-stirring mixing device and stirring and mixing to obtain a mixture; S2: conveying the mixed material to a mixing chamber for mixing, and conveying the mixed material to a twin-roll extruder for mixing to obtain a mixed material; S3: The mixed material is conveyed to a laminating machine for laminating, and the PVC film formed by laminating is laminated onto the base fabric while hot, and then cooled by a cooling roller to obtain a wall cloth.
5. The use according to claim 4, characterized in that: In step S1, the mixture is stirred and mixed at 40-50° C. for 4-10 minutes.
6. The use according to claim 4, characterized in that: In step S2, the mixture is kneaded at 130-140° C. for 5-10 min; the mixing time is 3-5 min.
7. The use according to claim 4, characterized in that: In step S3, the thermal paste bonding temperature is 165-185°C.
8. The use according to claim 4, characterized in that: After cooling, the method further comprises: printing and embossing by a gravure printing machine; wherein the printing temperature is 80-120° C., and the embossing temperature is 185-210° C.
9. The use according to claim 4, characterized in that: The preparation of the wall cloth also includes step S4: evenly coating the negative oxygen ion slurry on the surface of the wall cloth, drying and cooling, to obtain the negative oxygen ion wall cloth.
10. The use according to claim 9, characterized in that: The negative oxygen ion slurry comprises the following raw materials in parts by weight: 10-20 parts of negative oxygen ion material and 80-90 parts of printing medium; Preferably, the negative oxygen ion material comprises the following raw materials in parts by weight: 45-55 parts of modified acrylic emulsion, 0.5-1.5 parts of defoamer, 1.5-2.5 parts of N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate, 25-35 parts of modified nano-tourmaline powder and 15-25 parts of tert-butyl vinyl carbonate; Preferably, the modified nano-tourmaline powder is composed of nano-tourmaline powder and borate, and the weight ratio of the nano-tourmaline powder to the borate is (3-5): (5-7).